Pioneers : products from Phaidon design classics volume one. (London : Phaidon, 2006)
This volume demonstrates how the industrial revolution transformed the world of manufacturing. The technological advances it brought and the new cost-effective production techniques it utilized allowed a variety of goods to be affordable to ordinary people for the first time. During the nineteenth century.